The Influence of Company Size, Profitability, Liquidity, Leverage and Tax Avoidance Disclosure Against the Islamic Social Reporting on Companies Listed On The Indonesian Stock Index of Sharia - Siti Anita Wijayanti, Tutik Purwani, Nurlaela & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This research aims to identify the influence of company size, profitability,liquidity, leverage, and tax avoidance against the disclosure of Islamic socialreporting companies listed on the Indonesia Islamic stock index 2014-2016 period.The samples used in this study was 44 sample. Sample retrieval techniques in usingthe method of a purposive sample. Hypothesis testing in this study using multiplelinear regression tests. ISR was evaluated based on content analysis, by analyzingthe annual report of 18 sharia banks of 2014- 2017 period. In the checklist, thevalue of 1 was given for the report mentioning items of ISR and otherwise was 0.The results of this study with multiple regression tests shows simultaneouslythroughout the research variables affect the disclosure of Islamic Social Reportingwhile partially 1) effect on company Size disclosure ISR, 2) Profitability does noteffect disclosure ISR, 3) Liquidity has no effect against the disclosure ISR, 4)Leverage has no effect against the disclosure ISR .5) tax avoidance to disclosureISR.Keywords: Islamic Social Reporting, the size of the company, the companys performance